2015
DOI: 10.1136/bjsports-2014-094491
|View full text |Cite
|
Sign up to set email alerts
|

Muscle metabolism changes with age and maturation: How do they relate to youth sport performance?

Abstract: Aim: To provide an evidence-based review of muscle metabolism changes with sex-age-and maturation with reference to the development of youth sport performance. Methods:A narrative review of data from both invasive and non-invasive studies, from 1970-2015, founded on personal databases supported with computer searches of PubMed and Google Scholar.Results: Youth sport performance is underpinned by sex-age-and maturation-related changes in muscle metabolism. Investigations of muscle size, structure and metabolism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(50 citation statements)
references
References 96 publications
3
45
0
2
Order By: Relevance
“…In Japan, the 20mSRT is one of the physical fitness tests adopted by the Ministry of Education, Culture, Sports, Science and Technology and is conducted nationwide. It was demonstrated that children have unique physiological responses to exercise (Takagi et al ., ; Armstrong et al ., ; Pitt et al ., ) and that muscle oxygenation response during treadmill running in children is different from that in adults (Takagi et al ., ). Therefore, it is necessary to clarify the characteristics of muscle oxygenation profiles during the 20mSRT in children and its relationship with 20mSRT performance.…”
Section: Discussionmentioning
confidence: 99%
“…In Japan, the 20mSRT is one of the physical fitness tests adopted by the Ministry of Education, Culture, Sports, Science and Technology and is conducted nationwide. It was demonstrated that children have unique physiological responses to exercise (Takagi et al ., ; Armstrong et al ., ; Pitt et al ., ) and that muscle oxygenation response during treadmill running in children is different from that in adults (Takagi et al ., ). Therefore, it is necessary to clarify the characteristics of muscle oxygenation profiles during the 20mSRT in children and its relationship with 20mSRT performance.…”
Section: Discussionmentioning
confidence: 99%
“…Although it may seem inconsistent for less mature players (small forwarders and point guards) to outperform Yo-Yo IR1 in relation to more mature players (centers), it is likely that metabolic and neuromuscular changes that occur with maturation may be used as a justification to explain these results. Studies available in literature have shown that metabolic and neuromuscular changes that occur with the biological maturation process maximize the development of anaerobic metabolism and adversely influence energy production through aerobic metabolism 26,27 . For example, Doncaster et al 28 have shown that soccer players of the same chronological age classified as pre-PHV (less mature) have higher "efficiency" in using the oxidative system for energy production (represented by faster oxygen uptake kinetics) compared to players who were near or beyond PHV (more mature).…”
Section: Discussionmentioning
confidence: 99%
“…Throughout youth, the metabolic responses to exercise change with growth and maturation [102]. Following resistance and short-term high-intensity exercise, children have been shown to elicit lower post-exercise peak blood lactate concentrations, faster blood lactate clearance rates [67,75,[103][104][105][106][107][108][109], better blood acid-base regulation [110], lower phosphocreatine (PCr) depletion, faster PCr resynthesis rates [111][112][113][114] and faster heart rate recovery [67,75,108,115].…”
Section: Metabolic Responsesmentioning
confidence: 99%